Europe at a Crossroads: Failed Ideas, Fictional Facts, and Fatal Consequences - Thomasberger, Claus (Forum for Social Economics, 2015)
The crisis of the European Monetary Union has revealed the weakness and the fragility of the European integration process. The paper examines the institutional changes which are at the root of the instability. What are the driving forces behind the introduction of the euro? What role do theoretical considerations play in this process? What influence on European integration has been exerted by neoliberal beliefs and convictions? Relying on an approach that combines basic insights of Gunnar Myrdal with Karl Polanyi's idea of a "double movement," it concentrates on the institutional transformation that is at the basis of the European integration process. The relationship between (misleading) ideas and facts is at the center of the study. It examines the influence of ideas and theoretical models on European integration, the Single Market Program, the Maastricht process, the increasing imbalances since the introduction of the euro, and the strategies applied during the recent crisis.
Keywords: economic integration; financial aspects of economic integration; financial crises; international institutional arrangements

Żeby sprzedać – trzeba dać O rynku i jego nierynkowych fundamentach - Michalski, Michał A. (Prakseologia, 2015)
The paper analyzes interdependence of the market sphere which functions according to the logic of contract, and the sphere of non-market activity within economy, where the logic of gift dominates as a paradigm. The purpose of the analysis is to present how the above concepts of societal exchange intertwine and complete each other within the socio-economic order. This is followed by the description of 'pre-market' economic paradigms (based on Karl Polanyi's contribution) such as reciprocity, redistribution and household. Special attention is paid to category of gift, which is presented as prior to contract and being a necessary condition of the former one. The purpose of the analysis undertaken in this paper is to show how understanding of the interaction discussed here is necessary for creating integrated vision of how socio-economic order functions and offers adequate perspective for formulating recommendations within social and economic policy. (English) "To Sell One Has to Give – of Market and Its Non-Market Foundations"
Keywords: contract; economy; gift; gospodarka; kontrakt; market; rynek; socio-economic order; ład społeczno-gospodarczy

Toward a Sartrean Economics - Kail, Michel; Sobel, Richard (Rethinking Marxism, 2015)
Despite the absence of a systematic analysis of economics in Sartre's work, we argue that a Sartrean economics can indeed be said to exist, even if it is an economics that still awaits development. The status that Sartre accords to the concept of scarcity allows him to advance the critique of economism begun by Karl Polanyi, who, for his part, had been satisfied simply to challenge the reduction of economics to its formal definition. Scarcity, Sartre teaches us, should not be submitted to the process of instrumental reason but should be considered as a fact of human history. Economic analysis, meanwhile, should not be based solely on the theme of man's confrontation with a typically ungrateful nature but should rather be articulated through the concept of the world as elaborated in Sartrean philosophy.
Keywords: POLANYI, Karl, 1886-1964; SARTRE, Jean-Paul, 1905-1980; economic systems; economism; scarcity; world